(untitled) (Journal of Applied Oral Science, 2022)
Quantification of collagen degradation is an important parameter to evaluate dentin caries for preventive aid. Objectives: Evaluate preventive methods against root collagen degradation by the hydroxyproline assay (HYP) and microradiography technique (MRT). Methodology: Five bovine root dentin blocks were obtained and subjected to an artificial demineralization process by acetate buffer (pH 5) to induce carious lesion formation. Samples were subjected to the following therapeutic treatments: 1) 0.12% chlorhexidine for 1 min, 2) 2% fluoride for 1 min, 3) Nd:YAG Laser (400 μm diameter optical fiber, 10 Hz frequency, 60 mJ/pulse energy, 48 J/cm2 energy density, in noncontact mode for 10 s), 4) deionized water (control) for 1 min, 5) MRT control group (without treatment and removal of collagen). Samples were exposed to degradation by a collagenase enzyme for five days. The enzyme solution was collected, by colorimetry in a spectrophotometer, from the collagen matrix for the hydroxyproline release analysis. The same samples were subjected to an additional two days of demineralization to induce the progression of mineral loss. Samples were analyzed by MRT for the visualization of their degraded areas (estimation of lesion depth and mineral loss). ANOVA was applied to compare hydroxyproline release rates. MRT data were subjected to the Kruskal-Wallis test, followed by the Dunn’s test. Comparisons between the initial five-day and the subsequent two-day demineralization processes were performed by repeated t-test or Wilcoxon (p<0.05) measurements. Results: The amount of HYP released from the dentin samples failed to show significant differences among the groups (p=0.09). Fluoride and chlorhexidine were able to interact with the samples, reducing the progression of dentin caries after removal of the demineralized organic matrix. CHX was the only treatment able to show significant lower lesion depth than the negative control. Conclusion: Chlorhexidine and fluoride were effective in reducing root caries progression.